(untitled) (Al-Academy, 2025)
Assistive technology lies in designing innovative and multi-use furniture for the category of pilgrims, who are considered special categories according to the modern concept, as stated in the studies, in order to create a comfortable design atmosphere that facilitates the performance of high-quality Hajj rituals. The research aimed to design innovative multi-use furniture using assistive technology for the category of pilgrims to the House of God in the pilgrims’ residences in Makkah Al-Mukarramah, in line with the 2030 vision of the Kingdom of Saudi Arabia. The importance came in designing innovative multi-use furniture using assistive technology for the category of pilgrims to the House of God in the pilgrims’ residences to enhance moral and physical comfort. The study also followed the descriptive analytical approach represented in describing and analyzing the design by collecting data and presenting innovative designs in order to achieve the goal of the study. The results showed the positivity of the proposed design and its contribution to meeting the needs of the pilgrims. As for the recommendations, they came with the importance of conducting studies in the field of interior design for pilgrims’ housing in line with achieving the 2030 vision of the Kingdom of Saudi Arabia.